Sovereign risk, European crisis resolution policies and bond yields - Juha Kilponen; Helinä Laakkonen; Jouko Vilmunen (Bank of Finland, 2012)
We study the effects of the ECB monetary policy and the European crises resolution policies on the 10 year sovereign bond yields of seven European countries. We find that some of the decisions have had significant impact on sovereign bond yields and have succeeded in reducing stress in the financial markets. However, the impact of the same policy decision might have been positive for some countries while negative for others, suggesting that contagion effects may be important. The economically most significant effects on the bond yields have been due to the announcement of ECB's Securities Market Programme.
URN:NBN:fi:bof-20140807600
Keywords: 330